LANGUAGE DIVERSITY IN A MULTICULTURAL COMMUNITY LIVING ON WETLANDS IN THE CITY OF BANJARMASIN - Yuliana, Delva (International Conference On Social Science Education, 2023)
The people who live in Banjarmasin are classified as multicultural. Various tribes live in Banjarmasin City. Apart from the Banjar tribe, there are also Dayak tribes, Javanese tribes, Madurese tribes, Sundanese tribes, Bugis/Makasar tribes, Sundanese tribes, Minang tribes, Chinese tribes, and others. In general, they are classified as multi-ethnic. Such characteristics of society will undoubtedly result in language selection in their daily activities, whether in education, government or the family realm. This research examines the language choices of multicultural communities in Banjarmasin City in the family, school, and government domains. Banjar language is a family/branch of languages developed from Malay. It is also essential for the Banjar community to help strengthen the Banjar language, with the large-scale transmigration in the South Kalimantan region, so that the diversity of the Banjar language is maintained from generation to generation.